Kesehatan Terawat, Lingkungan Terlindungi: Kebersihan Sebagai Investasi Bersama - Nasrizal Nasrizal; Nur Adh Dhuha; Muhammad Ihsan; Syadzahara Nurul Chalifah; Rissika Priutami; Ihsana Arifa; Zariami Zariami; Diva Zahira; Muhammad Idris; Silas Yusthinus Baransano; Yohana Okoka (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This journal discusses student KKN activities at UNRI SUKAJADI VILLAGE, which is in Sukajadi Village, Bukit Batu District, Bengkalis Regency. Nowadays, cleanliness is considered trivial, so many local people don't care about cleanliness. Even though cleanliness is very important in life, both for health and the environment. Cleanliness affects health, as does the environment. A clean and healthy environment also improves the quality of life, fresh air, clean water and beautiful nature can improve physical and mental well-being. A healthy environment is the key to balance in an ecosystem. So the Kukerta group built the Sukajadi village and created a mutual cooperation work program at Datuk Laksamana gate. The aim of this work program is to raise public awareness about the environment because the environment is the key to creating a better, healthier and more sustainable world for all living creatures. Protecting the environment is our shared responsibility for future generations. Apart from that, the Sukajadi village community can overcome and invite the local community to clean around the Datuk Laksamana gate because cleaning the road at the Datuk gate is a simple but very important action that can have a big positive impact on human health and the environment.